Não era amor, era cilada: startups, coworkings e a mobilização do desejo pelo mundo do trabalho - Zanon, Breilla Valentina Barbosa (2019)
The aim of this paper is to think about the ways in which it was possible to mobilize and adjust the workers’ subjectivity to the discourse and business literature taken as reference by the new forms of post-fordist management of the work. Through field observations, interviews with startups entrepreneurs located in coworking spaces and theoretical revision, we will try to understand how these new models of flexible work enable workers - especially those linked to the dimension of creative and immaterial work - to internalize discourses that connect their desires and affections to the dimension of the work. In this way, we want to 1st) demonstrate the convergence of the emergence of the first startup and coworking spaces, observing how, as a result, the coworking spaces collaborate to maintain the enterprising atmosphere of the startups and, 2nd) to answer in which ways the worker’s love in relation to the conditions and results of his work works as ideological “cement” for new forms of labor exploitation. In this exercise, we observe that the concept of alienation developed by Karl Marx takes on new dimensions from the mobilization of subjectivities, naturalizing the processes of expropriation and exploitation understood now as creativity and innovation. So bringing this whole context is important to understand the basis of our hypothesis today: the individual, a worker with flexible working models, does not consider himself disconnected from what he produces, but in other hand, he identifies himself so completely with his work that he ends up not knowing or even admitting the conditions of work to which it is subjected, in which daily days, weekly rest and personal life are subordinated to the needs of the realization of projects, in a daily life marked by instabilities, fragilities and precariousness. We work with the hypothesis that such subjectivity is related to a rationality where the worker becomes an entrepreneur and mobilizes their desires, affections and other subjective aspects in function of a higher productivity within the work. We understand that the spaces of coworking are privileged places to carry out the analyzes, since in these spaces we find a working model, as the startups, that are born from the economic and productive transformations and puts at stake a worker profile that, under flexible conditions of work, internalizes discourses and practices that increasingly blur the boundaries between his life and his work, thus softening situations of conflict and exploitation.